The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/vetsci8050083
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Obstruction Induced by Concurrent Postoperative Intra-Abdominal Adhesions and Small Bowel Fecal Materials in a Young Dog

Abstract: A 7-month-old neutered male poodle dog presented with general deterioration and gastrointestinal symptoms after two separate operations: a jejunotomy for small-intestinal foreign body removal and an exploratory laparotomy for diagnosis and treatment of the gastrointestinal symptoms that occurred 1 month after the first surgery. The dog was diagnosed as having small-bowel obstruction (SBO) due to intra-abdominal adhesions and small-bowel fecal material (SBFM) by using abdominal radiography, ultrasonography, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In mammals, extensive reports have indicated that ABO is associated with cardinal symptoms such as acute or chronic abdominal pain, vomiting, and decreased oral input [16][17][18]. We believe that these complications may have also affected the NRFP in the present report.…”
Section: Discussionmentioning
confidence: 61%
“…In mammals, extensive reports have indicated that ABO is associated with cardinal symptoms such as acute or chronic abdominal pain, vomiting, and decreased oral input [16][17][18]. We believe that these complications may have also affected the NRFP in the present report.…”
Section: Discussionmentioning
confidence: 61%